Save-Child Application to Introduce Self-Protection to Children: Preliminary Study of Website-Based Learning Media - Madya Gerda, Misselina; Syamsuddin, Amir (Jurnal Pendidikan Usia Dini, 2023)
Digital transformation in the Society 5.0 era presents challenges for the world of education, especially teachers. The condition of early childhood education in Indonesia is worrying, data from the Online Women and Children Protection Information System (Simfoni-PPA) shows a significant increase in cases of sexual violence against children in 2019-2023. This research aims to collect and analyze product development needs from an early age, especially in introducing self-protection to young children. The Borg and Gall development model was used to develop the web-based Save-Child application. The results of this research only discuss the first stage of application development, namely needs analysis. The study presents a descriptive analysis regarding the development needs of the Save-Child application. This highlights that self-protection material has been taught but has not used modern digital-based media. The results of the study become the basis for designing application development that meets the needs and tendencies of teachers and children in early childhood education environments. Keywords: learning media, save-child website, self-protection, early childhood References: Adel, A. (2022). Future of industry 5.0 in society: human-centric solutions, challenges and prospective research areas. Journal of Cloud Computing, 11(1). https://doi.org/10.1186/s13677-022-00314-5 Aldhafeeri, F. M., & Khan, B. H. (2016). Teachers’ and Students’ Views on E-Learning Readiness in Kuwait’s Secondary Public Schools. Journal of Educational Technology Systems, 45(2), 202–235. https://doi.org/10.1177/0047239516646747 Andi. (2006). Panduan lengkap menguasai pemrograman web dengan PHP. Wahana Komputer. Assink, anne G. · C. E. van der P. · G. J. M. S. · M. (2021). Efective Components of School‑Based Prevention Programs for Child.pdf. https://doi.org/https://doi.org/10.1007/s10567-021-00353-5 Astuti, W., & Lita Hadiati, R. (2018). The Effectiveness of Sex Education to Increase Personal Safety Skill. International Research Journal of Advanced Engineering and Science Journal of Advanced Engineering and Science, 3(2), 155–156. http://www.nationalchildrenalliance.org/ Barrera, M., Calderón, L., & Bell, V. (2013). The cognitive impact of sexual abuse and PTSD in children: A neuropsychological study. Journal of Child Sexual Abuse, 22(6), 625–638. https://doi.org/10.1080/10538712.2013.811141 Bright, M. A., Roehrkasse, A., Masten, S., Nauman, A., & Finkelhor, D. (2022). Child abuse prevention education policies increase reports of child sexual abuse. Child Abuse and Neglect, 134(June), 105932. https://doi.org/10.1016/j.chiabu.2022.105932 Brown, D., & De Cao, E. (2017). The Impact of Unemployment on Child Abuse and Neglect in the United States. System (NCANDS), 1–44. Buckley, H. (2007). Listen to Me ! Children ’ s Experiences of. 16(January 2008), 296–310. https://doi.org/10.1002/car Charlotte Reznick. (2009). Transform stress and anxiety into joy and success (Pertama). Tarcher Perigee. christopher bagley, kathleen king. (2004). Child sexual abuse the search for healing. In Angewandte Chemie International Edition, 6(11), 951–952. (Vol. 3, Issue 1). Taylor & Francis e-Library. https://library.lol/main/ED7362B4D86B0BE574E2B030177654A3 Das., L. A. K. J. M. (2023). Prevention Strategies. StatPearls Publishing. de Jong, R., Alink, L., Bijleveld, C., Finkenauer, C., & Hendriks, J. (2015). Transition to adulthood of child sexual abuse victims. Aggression and Violent Behavior, 24, 175–187. https://doi.org/10.1016/j.avb.2015.04.012 Decker, M. J., Harrison, S., & Tenney, R. (2021). Educators ’ perspectives on integrating technology into sexual health education : implementation study international registered report identifier ( IRRID ) Intervention Overview. Diane O’Doherty, M. D., Lougheed, J., Hannigan, A., & McGrath, J. L. and D. (2018). Barriers and solutions to online learning in medical education-an integrative review. BMC Medical Education, 11(22), 832–834. Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review, 118(June), 105440. https://doi.org/10.1016/j.childyouth.2020.105440 Erdianti, R. N., & Al-Fatih, S. (2020). Children Friendly School as the Legal Protection for Children in Indonesia. Varia Justicia, 16(2), 137–155. Finklehor D. (1984). child sexual abuse : new theory and research. free press. Freedoms, F., Hourcade, J. P., Gilutz, S., Yoon, K., Asriyatun, A., Nugroho, M. A., Justicia, R., Matthews, P. H., Zeller, H., Ogunjimi, A. I., Abadio De Oliveira, W., Maria, E., De Vasconcelos, R., Angelica, M., Silva, I., Kemdikbudristek, Dewi, C. K., كريستينا، رود. كوكورس, Lin, M. H., … Anwar Setiadi1, Drs. Pitoyo Yuliatmojo, M.T.2, Diat Nurhidayat, M. T. . (2020). International technical guidance on sexuality education. United Nations Educational Scientific and Cultural Organization SDGs, 9(1), 1–139. https://doi.org/10.1016/j.childyouth.2020.105227 Guernsey. (2013). Electronic Media and Language Development-0- 3. New Found. José de Valverde, Laurent Sovet, T. L. (2012). Life Design: In Journal of Counseling & Development (Issue 1). Elsevier Inc. https://doi.org/10.1016/B978-0-12-809790-8/00006-6 Kandi, Z. R. K., Azar, F. E. F., Farahani, F. K., Azadi, N., & Mansourian, M. (2022). Significance of Knowledge in Children on Self-Protection of Sexual Abuse: A Systematic Review. Iranian Journal of Public Health, 51(8), 1755–1765. https://doi.org/10.18502/ijph.v51i8.10257 Kementerian Pendidikan dan Kebudayaan. (2017). Direktorat Pembinaan Pendidikan Anak Usia Dini Direktorat Jenderal Pendidikan Anak Usia Dini dan Pendidikan Masyarakat Kementerian Pendidikan dan Kebudayaan. 021. Kementrian Pemberdayaan Perempuan dan Perlindungan Anak. (2023). Data statitstik kasus kekerasan di indonesia. https://kekerasan.kemenpppa.go.id/ringkasan Kenny, M. C., Helpingstine, C., & Long, H. (2020). College students’ recollections of childhood sexual abuse prevention programs and their potential impact on reduction of sexual victimization. Child Abuse and Neglect, 104(October 2019), 104486. https://doi.org/10.1016/j.chiabu.2020.104486 Laukkanen, A., Niemistö, D., Aunola, K., Barnett, L. M., & Sääkslahti, A. (2023). Child perceived motor competence as a moderator between physical activity parenting and child objectively measured physical activity. Psychology of Sport and Exercise, 67(June 2022). https://doi.org/10.1016/j.psychsport.2023.102444 Maryatun, I. B. (2016). Peran Pendidik Paud Dalam Membangun Karakter Anak. Jurnal Pendidikan Anak, 5(1), 747–752. https://doi.org/10.21831/jpa.v5i1.12370 McKee, B. E., & Dillenburger, K. (2012). Effectiveness of child protection training for pre-service early childhood educators. International Journal of Educational Research, 53, 348–359. https://doi.org/10.1016/j.ijer.2012.04.008 Miles, M. B. and A. M. H. (2005). Qualitative Data Analysis (terjemahan). UI Press. Muhammad, H. (2022). PANDUAN PENYELENGGARAAN PAUD BERKUALITAS Seri Ke 2. Kemitraan Dengan Orang Tua, 1, 1–59. Nanang. (2020). Media interaktif pendidikan seks tentang deteksi dini kekerasan seksual pada anak untuk guru sekolah dasar. 702015019. Noble-Carr, D., Moore, T., & McArthur, M. (2020). Children’s experiences and needs in relation to domestic and family violence: Findings from a meta-synthesis. Child and Family Social Work, 25(1), 182–191. https://doi.org/10.1111/cfs.12645 Øverlien, C., & Holt, S. (2019). Letter to the Editor: Research on Children Experiencing Domestic Violence. Journal of Family Violence, 34(1), 65–67. https://doi.org/10.1007/s10896-018-9997-9 Papadakis, S., Kalogiannakis, M., & Zaranis, N. (2018). Educational apps from the Android Google Play for Greek preschoolers: A systematic review. Computers and Education, 116, 139–160. https://doi.org/10.1016/j.compedu.2017.09.007 Putri, G. A. B. A. (2022). Sex Education in Elementary School To Prevent Sexual Abuse of Children. Progres Pendidikan, 3(1), 7–11. https://doi.org/10.29303/prospek.v3i1.220 Russell, D., Higgins, D., & Posso, A. (2020). Preventing child sexual abuse: A systematic review of interventions and their efficacy in developing countries. Child Abuse and Neglect, 102(August 2019), 104395. https://doi.org/10.1016/j.chiabu.2020.104395 Sari, M. W., Adhani, D. N., & Karim, M. B. (2021). Peran Guru dalam Penerapan Sekolah Ramah Anak di TK YKK 1 Bangkalan. Jurnal PG-PAUD Trunojoyo : Jurnal Pendidikan Dan Pembelajaran Anak Usia Dini, 8(1), 8–14. https://doi.org/10.21107/pgpaudtrunojoyo.v8i1.9088 Schlichting, L. E., Vivier, P. M., Berger, B., Parrillo, D., & Sheldrick, R. C. (2022). From Descriptive to Predictive: Linking Early Childhood Developmental and Behavioral Screening Results With Educational Outcomes in Kindergarten. Academic Pediatrics, 000. https://doi.org/10.1016/j.acap.2022.07.022 Selwyn, N. (2006). Exploring the “digital disconnect” between net-savvy students and their schools. Learning, Media and Technology, 31(1), 5–17. https://doi.org/10.1080/17439880500515416 Stevenson, M. (2013). UvA-DARE (Digital Academic Repository). Tiara Anvadilla. (2022). Pengembangan Website Mengenai Regulation Perserta Didik Kelas Viii Regulation Perserta Didik Kelas Viii. UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG. Widayanti, Y., & Rahmawati, S. (2022). Gesit Edusex: Pengembangan Media Berbasis Google Sites Sebagai Media Pengetahuan Seks Di Kalangan Mahasiswa. JURNAL PAJAR (Pendidikan Dan Pengajaran), 6(4), 1245. https://doi.org/10.33578/pjr.v6i4.8841 Widayati, J. R., Safrina, R., & Supriyati, Y. (2020). Analisis Pengembangan Literasi Sains Anak Usia Dini melalui Alat Permainan Edukatif. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 654. https://doi.org/10.31004/obsesi.v5i1.692 Yulianti, A., & Ekohariadi, E. (2020). Pemanfaatan Media Pembelajaran Berbasis Game Edukasi Menggunakan Aplikasi Construct 2 pada Mata Pelajaran Komputer dan Jaringan Dasar. Jurnal IT-EDU, 5(1), 527–533. https://ejournal.unesa.ac.id/index.php/it-edu/article/view/38272